Low-cost Device to Upcycling PET Plastic Bottle Into 3D Printer Filament - Rodiana, Irham Mulkan; Pramudita, Brahmantya Aji; Barokatillah, Nyimas Anggun; Abd. Rahman Saleh; Aghesa Tri Nirbhita Daniswara (Emitor: Jurnal Teknik Elektro, 2025)
Plastic waste poses a substantial risk, causing blockages in water channels and contributing to flooding incidents. The accumulation of plastic bottles, which can take 450 to 1000 years to decompose, accelerates environmental degradation. The Ministry of Environment and Forestry (KLHK) supports waste utilization industries through the 3R principle (Reuse, Reduce, Recycle), with recycling offering a sustainable way to reuse materials. The advent of Industry 4.0 brings technological advancements, particularly in 3D printing through the FDM method. Addressing this issue requires more efficient waste management, promoting the use of refillable bottles, seeking eco-friendly packaging materials, and recycling PET bottles into 3D printing filaments. This approach provides low-cost value, reducing dependence on virgin materials and cutting waste. Additionally, the development of a mobile app adds integrated value, enabling users to efficiently set up devices for optimized filament production. A clean and sustainable environment necessitates full support from government policies and collaboration among the government, industry, and the community. Filament testing from plastic bottles reveals variations in diameter based on experimental speed. At 4 RPM, the filament measures 1.6 mm, while other speeds result in approximately 1.7 mm. The combination of 2 RPM speed and a temperature of 200°C, and 3 RPM speed with a temperature of 210°C, proves most suitable for high-quality 3D printing of Vase and 3D Benchmark from plastic bottles.